Determinan Kualitas Hidup Pasien Pasca Operasi Kanker Payudara di Indonesia: A Systematic review - Made Agus Suanjaya; Ayu Anulus; Besar Tirto Husodo (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The quality of life of breast cancer patients post-surgery is an important indicator in assessing the success of long-term management, particularly in Indonesia, which has a high prevalence of breast cancer. This systematic review aims to identify the determinant factors affecting the quality of life of post-surgery breast cancer patients in Indonesia. Literature searches were conducted through PubMed, Google Scholar, and grey literature databases using Boolean operator keywords. The search was conducted without publication year restrictions, but only articles up to July 2025 were included. Of the 1,258 articles identified, 8 studies met the inclusion criteria and were analyzed narratively. Articles were also critically assessed for quality using JBI based on their study design. All articles had an average quality of moderate-high in reporting their research. The findings of the studies indicate that the quality of life of post-surgery breast cancer patients is influenced by physical, psychological, social, and medical factors. Low physical activity, anxiety, depression, and poor body image can reduce the quality of life. Social support from family and community helps improve the patient's well-being. Additionally, breast reconstruction can enhance the quality of life, though not all patients choose to undergo this procedure. In conclusion, interventions that consider physical, psychological, social, and medical factors should be integrated into post-surgery breast cancer care in Indonesia to improve the patient's quality of life holistically.